2005
DOI: 10.1007/s11267-005-3013-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of land use on soluble organic nitrogen in soil

Abstract: Although it has been hypothesized that soluble organic nitrogen (SON) plays a central role in regulating productivity in some terrestrial ecosystems, the factors controlling the size of the SON pool in soil remain poorly understood. Therefore our principal aim in this work was to assess the impact of seven different land use systems (rough and managed grassland, deciduous and coniferous woodland, heathland, wetland and tilled land) on the size of the SON and inorganic N (NO − 3 , NH + 4 ) pools in the surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…On a comprehensive consideration of the most probable factors, the abnormal abundance of soil SON in the present study might have resulted from: i) the 0-15cm mineral soils in this study were typically characterized by high organic matter and high organic nitrogen content (3.81-7.95g·kg -1 ), which might have brought high SON consequently; ii) the sampling date was just after the freeze-thaw season and the temperature of mineral soils was still too low to generate a soil microbial flush or enable any significant activity of soil enzymes responsible for SON transformation, thus, some organic nitrogen leached from organic layer, or released by freeze-thaw events (including low molecular humic nitrogen and bio-nitrogen) might temporarily accumulate as "soluble" in surface mineral soils. The spacial variation in SON pools observed in the present study was analogical to many other reports (Hannam and Prescott 2003;Zhong and Makeschin 2003;Willett et al 2004;Chen et al 2005;Berthrong and Finzi 2006), and it could be attributed to a combination of factors including soil types (N quantity and quality), tree species (leaf and root litters), management levels and environmental conditions (temperature and moisture).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…On a comprehensive consideration of the most probable factors, the abnormal abundance of soil SON in the present study might have resulted from: i) the 0-15cm mineral soils in this study were typically characterized by high organic matter and high organic nitrogen content (3.81-7.95g·kg -1 ), which might have brought high SON consequently; ii) the sampling date was just after the freeze-thaw season and the temperature of mineral soils was still too low to generate a soil microbial flush or enable any significant activity of soil enzymes responsible for SON transformation, thus, some organic nitrogen leached from organic layer, or released by freeze-thaw events (including low molecular humic nitrogen and bio-nitrogen) might temporarily accumulate as "soluble" in surface mineral soils. The spacial variation in SON pools observed in the present study was analogical to many other reports (Hannam and Prescott 2003;Zhong and Makeschin 2003;Willett et al 2004;Chen et al 2005;Berthrong and Finzi 2006), and it could be attributed to a combination of factors including soil types (N quantity and quality), tree species (leaf and root litters), management levels and environmental conditions (temperature and moisture).…”
Section: Resultssupporting
confidence: 89%
“…A recent study on surface forest soils of subtropical Australia reported that the concentrations of SON extracted by 2 M KCl, 0.5 M K 2 SO 4 and water was 5-45 mg·kg -1 , 2-42 mg·kg -1 and 1-24 mg·kg -1 , respectively (Chen et al 2005). Water extracted SON from soils is less efficient than salt solutions due to the fact that salt solutions have greater potential for cation/anion exchange reactions leading to liberate physically adsorbed SON from clay minerals and/or soil organic matter, and the SON extracted by water was generally 20%-40% (about one-third on average) of SON extracted by salt solutions (Hannam and Prescott 2003; Willett et al 2004;Chen et al 2005). The water soluble SON pools in organic layers measured in this study were within the similar magnitude of salt solution extracted SON pools reported in the literature as above, while the water soluble SON in 0-15 cm mineral soils here were much higher (3-10 times) than any other reported soils, irrespective of forest and soil types and extraction methods (water or salt solutions), as discussed above.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, increasing application of conservation tillage, organic farming, and other nontraditional agronomic practices may be expected to increase the importance of DON in agricultural runoff. DON also needs to be incorporated into watershed models because it is important to the N cycling of various natural watershed ecosystem components (Timperley et al, 1985;Schoenau and Bettany, 1987;Phipps and Crumpton, 1994;Hedin et al, 1995;Stepanauskas et al, 1999;Qualls, 2000;Willett et al, 2004).…”
Section: Nitrogenmentioning
confidence: 99%
“…To a large extent, this is due to the chemical complexity of high‐MW components, which are thought to constitute a large proportion of the DOM in soil. The composition and behavior of DOM can also be highly variable in soil, being dependent on many factors including land use and management (Macdonald et al, 2007; Willett et al, 2004a,b), the organic matter source (e.g., allochthonous or autochthonous), climate (e.g., temperature and precipitation), soil chemistry (e.g., ionic strength, pH, and surface chemistry), biological activity (e.g., microbial activity), and physical factors (e.g., bulk density) (Leenheer and Croué, 2003; Marschner and Kalbitz, 2003). The major problem in addressing the issue of the physicochemical composition of the DOM pool is therefore the lack of an all‐encompassing analytical tool capable of identifying the multitude of chemicals present within the organic matrix.…”
mentioning
confidence: 99%
“…Dissolved organic C and N represent an abundant form of soluble nutrients and energy supply for soil microorganisms and play an important role in nutrient cycling in ecosystems (Murphy et al, 2000; Nashölm et al, 2009). In some ecosystems, losses of DON from the soil (i.e., by leaching and runoff) may exceed those of inorganic nutrients (Willett et al, 2004a,b). While the temporal dynamics of DOC and DON have frequently been studied, particularly in forest soils (Michalzik et al, 2001), relatively little is known about the chemical constituents of these pools and thus their functional significance (Jones et al, 2005a).…”
mentioning
confidence: 99%